CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN NOUN PHRASE - Budi Susatyo; Dholiful Hadi; Syahril Roziqi (Universitas PGRI Ronggolawe Tuban, 2023)
The main goal of this research is intended to find the differences and similarities between English and Indonesian noun phrases. The problem to study is to know the patterns of English and Indonesian Noun Phrases. However, it will be detected the similarities and differences between the two languages. The patterns of English and Indonesian Noun Phrases are analyzed by using combination English and Indonesian Noun Phrases. The data, the writer uses contrastive analysis method to determine their similarities and differences; the source of the research; understanding English grammar, vocabulary, basic English usage, introduction to linguistic; and Tata Bahasa Praktis Bahasa Indonesia and syntaxes all data collected above are analyzed by contrastive analysis. The result of the data analysis reveals that there are differences between English and Indonesian Noun Phrases; namely; adjective as modifier; possessive adjective or possessive noun as modifier; participate as modifier, noun as modifier and adverb as modifier. Meanwhile, there are three kinds of similarities that is 1) the similarities of Head-Modifier; the similarities of Modifier-Head and the similarities of Modifier-Head-Modifier, 2) the similarities element forming noun phrases, namely prepositional phrases, adverbs, numerals, noun, demonstrative adjective, indefinite adjective and non-finite clause, 3) the similarities in order of element forming noun phrases; namely the order of determiner and the order of modifier. By knowing the differences and the similarities above; it is expected that the teacher can explain the noun phrases both English and Indonesian well.